2021
DOI: 10.1155/2021/6927985
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Iran: Forecasting Pandemic Using Deep Learning

Abstract: COVID-19 has led to a pandemic, affecting almost all countries in a few months. In this work, we applied selected deep learning models including multilayer perceptron, random forest, and different versions of long short-term memory (LSTM), using three data sources to train the models, including COVID-19 occurrences, basic information like coded country names, and detailed information like population, and area of different countries. The main goal is to forecast the outbreak in nine countries (Iran, Germany, It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…The results indicated that with a root mean square error of 12.3, the Holt-winter model can be a good predictor of COVID-19 deaths cases in Iran. Kafieh et al (2021) provided a similar study concerning COVID-19 trend forecasting in Iran as well as other countries. The results demonstrated that with a root mean square error of 458.12, the multivariate long short-term memory is the optimal choice.…”
Section: Literature Surveymentioning
confidence: 93%
“…The results indicated that with a root mean square error of 12.3, the Holt-winter model can be a good predictor of COVID-19 deaths cases in Iran. Kafieh et al (2021) provided a similar study concerning COVID-19 trend forecasting in Iran as well as other countries. The results demonstrated that with a root mean square error of 458.12, the multivariate long short-term memory is the optimal choice.…”
Section: Literature Surveymentioning
confidence: 93%
“…Additionally, In Kafieh et al (2021) [ 25 ], the main objective was to predict outbreaks in nine countries - Iran, Germany, Italy, Japan, Japan, Korea, Switzerland, Spain, China, and the United States of America. Data between 22 January and 30 July 2020 were used for training and the period 1–31 August 2020 for testing.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the infection rate fell to 65% after implementing global travel restrictions [2]. COVID-19 also spread to different parts of Asia, and the number of infections was very high in Turkey, India, Indonesia, and Iran [3][4][5][6]. The middle to low-income countries in Asia and the Asia-Pacific regions were the worst affected [6].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 also spread to different parts of Asia, and the number of infections was very high in Turkey, India, Indonesia, and Iran [3][4][5][6]. The middle to low-income countries in Asia and the Asia-Pacific regions were the worst affected [6]. However, some success stories in controlling the spread of the disease are from small Asian countries such as Taiwan, Vietnam, and South Korea [7].…”
Section: Introductionmentioning
confidence: 99%